The Machine Tool Industry Problems and Prospects in an International Perspective - Bo Carlsson (The Research Institute of Industrial Economics (IUI), 1983)
The machine tool industry is tiny but crucial: it supplies the machines to cut, form, and shape metals upon which about half of the manufacturing industries are dependent. The state of the art of the machine tools themselves, their control systems and the organization surrounding them largely determine the productivity and competitiveness of engineering industries in general. The machine tool industry faces two major challenges today. One is that technological change in machine tools has changed character in recent years. After more than a century of evolutionary progress, mainly involving mechanization and improved control of mass production, the main progress in machine tools in the last two decades has involved automation and mechanization of small and medium scale production, largely in connection with the introduction of numerical control and also other aspects of the microelectronic revolution. This change in the character and direction of technological change is forcing profound changes both within the industry and in its relationship with users. The other problem is that the competitive situation in the world market is changing rapidly, causing severe adjustment problems for most producers. Even though this is an industry in which foreign trade has always been significant, the emergence of new competitors (particularly Japan in numerically controlled machine tools and newly industrialized countries in conventional machine tools) with new strategies and new kinds of specialization has made for radical changes in the competitive situation for most machine tool firms. One section of the paper deals with the strategies which machine tool firms in the United States and Sweden have chosen to deal with these challenges. This part of the study is based on firm interviews. The paper concludes with some thoughts on the likely results of the present changes for the machine tool industry of tomorrow.
Keywords: C42; L10; L61; 330; Manufacturing; Firm strategy; Survey